The experience of developing the skills of working with historical concepts of elementary school students of foreign countries - Qodirova Buzulaykho Turg‘unovna; Toshlanova Madina (Periodica Journal, 2024)
In this article, the experience of developing the skills of working with historical concepts of primary education students of foreign countries, modern textbooks of the new generation, Historical concept, historical memories and indelible memories of the legacy of our ancestors were discussed.
Keywords: discussed; ancestors; developing; concepts